To the top! : climbing the world's highest mountain - Kramer, Sydelle; LaPadula, Tom (New York : Random House, 1993)
Describes how Edmund Hillary and Tenzing Norkey became the first human beings to reach the top of the world by climbing Mount Everest.
"Grades 2-4"--Cover.
Bulletin (Center for Childrens's books)
4.3
K-3
Keywords: Hillary, Edmund, -- Sir -- Biography -- Juvenile literature; Tenzing Norkey, -- 1914- -- Biography -- Juvenile literature; Mountaineering -- Everest, Mount (China and Nepal) -- History -- Juvenile literature; Mountaineers -- Biography -- Juvenile literature; Hillary, Edmund, -- Sir; Tenzing Norkey, -- 1914-; Mountaineering -- Everest, Mount (China and Nepal) -- History; Mountaineers; Hillary, Edmund, Sir; Tenzing Norkey, -- 1914-; Mountaineering; Mountaineers -- Biography